Sport injuries in elite Paralympic judokas: Findings from the 2018 World Championship - Gutiérrez-Santiago, A.; Prieto-Lage, I.; Martin, A.; Ayán, C. (Journal of Physical Activity and Health, 2020)
Background: To provide information regarding injury incidence, injury pattern, and associated injury risk factors in elite Paralympic judokas. Methods: Participants in this observational research were elite judokas taking part in the IBSA 2018 World Judo Championship. The entire championship was videotaped, and all injuries were prospectively documented using an all-complaints definition. Results: The tournament featured 267 judokas, (B1 = 58; B2 = 105; B3 = 104). The injury proportion was estimated at 18.9 injuries/100 fighters (B1 = 13.8; B2 = 22.3; B3 = 18.5). A total of 745 athletic exposures were registered. The overall injury rate was 68.5 (95% CI, 52.5-89.2); 62.5 (95% CI, 32-122.3); 79.6 (95% CI, 53.8-17.8); and 61.2 (95% CI, 40-93.5) for the total sample, B1, B2, and B3 judokas, respectively. When only injuries resulting in medical attention were analyzed, the overall injury rate was calculated to be 22.8 (95% CI, 14.3-36.5), and the injury proportion was estimated at 6.3 injuries/100 fighters. No significant differences were found for sex, weight, and visual class regarding injury proportion and injury rates. Conclusion: Paralympic judokas show a high injury rate. However, when only injuries that needed medical attention were taken into account, the proportion of athletes injured was low. The degree of visual impairment was not considered as an injury risk factor.